The Problems of Mathematics Learning at Class V SDN 12 Sungai Sapih in Naterial of Calculation (Multlipication and Division) - Salmatun Zahra; Nuri Tiarani; Dini Sri Utami (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This study aims to analyze the mathematical learning problems of fifth grade students at SDN 12 Sungai Sapih in learning to count (multiplication and division). This type of research uses qualitative methods. Data collection techniques used in this study were observation, interview, and documentation techniques. The population and sample in this study were 1 teacher and 4 5th grade students at SDN 12 Sungai Sapih. The results of the study found that (1) students' perceptions of mathematics subjects in counting learning (multiplication and division) (2) The teacher's role in increasing the interest of fifth grade students at SDN 12 Sungai Sapih in Mathematics subjects in learning to count (multiplication and division). (3) Learning problems faced by students in Mathematics subjects in learning to count (multiplication and division) (4) Solutions to problems faced by students and teachers in the teaching and learning process in mathematics subjects in numeracy learning